Poland's noble son : life of St. Stanislaus Kostka - Mayer, Maxine; Daughters of St. Paul. (Boston, MA : St. Paul Books & Media, 1987)
A biography of a patron saint of Poland, whose childhood desire for holiness led him to have visions of angels and the Virgin Mary before he met his early death.
Keywords: Kostka, Stanislas, -- 1550-1568 -- Juvenile literature; Kostka, Stanislas, -- 1550-1568.; Christian saints -- Poland -- Biography -- Juvenile literature; Saints